Deteksi Kecurangan Laporan Keuangan Menggunakan Model Beneish M-Score Berdasarkan Perspektif Fraud Triangle pada Perusahaan Sektor Teknologi - Cresensia Benita Thendea; Hengky Leon (JUEB : Jurnal Ekonomi dan Bisnis, 2026)
This paper analyzed the identification of accounting fraud in the financial reports of technology companies listed on the Indonesian Stock Exchange between 2022 and 2024 and explored the impact of the fraud triangle model. A quantitative approach was employed, using a logistic regression model and SPSS software for evaluation. The study utilized 69 observations from 23 technology companies throughout the observation period. The variables examined represented the fraud triangle model: financial stability (stress), industry affiliation (opportunity), and the ratio of total appropriations to total assets (TATA, as a rationalization indicator). The results showed that financial stability had no impact on fraud indicators, indicating that stress is not a key factor in fraud occurrence. On the other hand, industry affiliation had a negative impact on accounting fraud, showing that opportunities arising from strict regulation can reduce the likelihood of fraud. TATA, however, had a positive impact on accounting fraud, indicating that rationalization is a contributing factor. This study contributes to the further development of research on the fraud triangle model, particularly in the Indonesian technology industry.